Research and analysis of dynamics of pump unit control process - Буравченко, Костянтин Олегович (Technology audit and production reserves, 2016)
This article analyzes the dynamics of the water supply system and shows the results of author’s research in this field. The main aim of this research is evaluation of the effect of pipeline parameters on stability of water supply system. It is necessary to find a pipeline length at which the water supply system remains stable. This article discussed the stability research of water supply system with pipeline connection via the Nyquist frequency method. The obtained dependence allows getting the pipeline length at which the system remains stable under any perturbations. Researches show that the pipeline parameters directly affect the stability of the system that need to be considered in the design of water supply systems. The author proposes to use the results for design of water distribution networks in order to ensure the stability of the control system. The research results can be used by designers of water supply systems, automation and remote control, engaged in the field of water supply.